2017
DOI: 10.1515/cdbme-2017-0122
|View full text |Cite
|
Sign up to set email alerts
|

In-ear photoplethysmography for central pulse waveform analysis in non-invasive hemodynamic monitoring

Abstract: Abstract:In recent years, the analysis of the photoplethysmographic (PPG) pulse waveforms has attracted much research focus. However, the considered signals are primarily recorded at the fingertips, which suffer from reduced peripheral perfusion in situations like hypovolemia or sepsis, rendering waveform analysis infeasible. The ear canal is not affected by cardiovascular centralization and could thus prove to be an ideal alternate measurement site for pulse waveform analysis. Therefore, we developed a novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 4 publications
2
20
0
Order By: Relevance
“…The models of Lognormal function have higher precision than the models of Gaussian function under the same model order, and the lognormal function is more suitable for ABP wave modeling. This conclusion is consistent with [21] and [22]. The two-sample ks-test results show that the parameters of all models are markedly different at a highly significant level (h = 1, p < 0.001, as shown in Table 6(a) to Table 7(b)).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The models of Lognormal function have higher precision than the models of Gaussian function under the same model order, and the lognormal function is more suitable for ABP wave modeling. This conclusion is consistent with [21] and [22]. The two-sample ks-test results show that the parameters of all models are markedly different at a highly significant level (h = 1, p < 0.001, as shown in Table 6(a) to Table 7(b)).…”
Section: Discussionsupporting
confidence: 83%
“…Wang et al [20] suggested that four-or five-Gaussian models have maximum accuracy. Tigges et al [16], [21] proposed that we can obtain a model with an arbitrarily small error simply by increasing the number of the kernel function, while it will lead to overfitting of data and consequently to the physiologically uninterpretable solution. Recently, Liu et al [17], [22] demonstrated that morphological models with three-Gaussian and three-Lognormal functions are better than that of Raleigh and double-exponential functions for healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen in table 1, there is a wide variety of suggested PWD algorithms in the literature that differ in the number and type of used kernels. Tigges et al (2017a) conducted a comparison of accuracy between several PWD algorithms and found an algorithm based on three Gamma kernels to achieve the best results. Huang et al (2015) examined the benefit of the usage of a mixture of Gamma and Gaussian kernels over pure Gaussian kernel-based algorithms and showed that the algorithm consisting of a Gamma kernel and three Gaussian kernels exhibited the best results in residual analysis.…”
Section: Background On Morphological Ppg Signal Analysis By Pwdmentioning
confidence: 99%
“…For the expression of the PDA model, there is a controversy with regard to the ideal number and type of kernel function. Tigges et al (2017aTigges et al ( , 2017b proposed that a model with an arbitrarily small error can be obtained simply by increasing the number of the kernel function, while it will lead to overfitting of data and consequently to a physiologically uninterpretable solution. Jiang et al (2018) demonstrated that the three Gaussian function model has better fitting accuracy and the obvious physiological implication after comparing four types of fitting functions, including Gaussian function, Raleigh function, double-exponential function and logarithmic normal function.…”
Section: Abp Wave Modeling and Parameter Estimationmentioning
confidence: 99%